Self-Control and Website Quality on Impulsive Buying of Shopee User Students - Hamid Cholili, Abd; Inayah, Inayah; Aghniacakti, Ainindita (Rifa'Institute, 2024)
This research aims to determine the influence of self-control and website quality on the impulsive buying of student Shopee users. Sampling used a purposive sampling technique with a total of 90 respondents and the data collection instrument used the impulse buying tendency scale (IBTS) from Verplanken and Herabadi, the self-control scale was prepared to refer to Averill's self-control aspect, and the website quality scale was prepared based on Kim's theory. and Niehm. The data analysis technique uses the Multiple Linear Regression Test. Based on the analysis data, a significance results of 0.000 was obtained, which is smaller than 0.05, meaning that self-control and website quality together influence impulsive buying. The calculated value of the coefficient of determination (R Square) is 0.806. This means that Self Control and Website Quality can influence 80.6% of Impulsive Buying while the remaining 19.4% is influenced by other variables not discussed in this research.